ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS MAKANAN DAN PELAYANAN RESTORAN GET STEAK DI KOTA MEDAN - Abdi, Fahmi Aditya; Nasution, Adelyna Oktavia; Harahap, Fauzi Syahputra; Siregar, Ummi Kalsum; Rahmadani, Nabila (Yayasan Amanah Nur Aman, 2025)
This study highlights the comparison of customer satisfaction with two main aspects of restaurant services, namely food quality and service quality. The study was conducted at all branches of Get Steak Restaurant in Medan City with a quantitative approach. The results show that food quality received a more positive response than service, although both were in the